Visually available order, categorisation practices, and perception-in-action: a running commentary. Issue 1 (2nd January 2019) - Smith, Robin James
Abstract : This article is concerned with perception and visually available order in running. It draws on ethnomethodological principles to analyse a commentary produced during a run through a city centre. In doing so, the article revisits and takes forward two articles previously published in this journal. The article discusses the radical ethnomethodological understanding of perception-in-action, before presenting an analysis of the running commentary that draws out the ways in which the describing of the commonplace scene exhibits the organisation of 'seeing' in terms of the practical relevance that elements of the visual environment have for the work of running. The analysis identifies various practices including, routing and navigation, the seeing of 'assemblies' of people and objects, and the categorial identification of individuals and groups. The article thus aims to demonstrate the local, categorial, and situated grounds of perception and the practical adequacy of observation in and through the work of a given activity.